Arabidopsis PROTEIN S‐ACYL TRANSFERASE4 mediates root hair growth. (13th March 2017) - Wan, Zhi‐Yuan; Chai, Sen; Ge, Fu‐Rong; Feng, Qiang‐Nan; Zhang, Yan; Li, Sha
Summary: Polar growth of root hairs is critical for plant survival and requires fine‐tuned Rho of plants (ROP) signaling. Multiple ROP regulators participate in root hair growth. However, protein S ‐acyl transferases (PATs), mediating the S ‐acylation and membrane partitioning of ROPs, are yet to be found. Using a reverse genetic approach, combining fluorescence probes, pharmacological drugs, site‐directed mutagenesis and genetic analysis with related root‐hair mutants, we have identified and characterized an Arabidopsis PAT, which may be responsible for ROP2 S ‐acylation in root hairs. Specifically, functional loss of PAT4 resulted in reduced root hair elongation, which was rescued by a wild‐type but not an enzyme‐inactive PAT4. Membrane‐associated ROP2 was significantly reduced in pat4, similar to S ‐acylation‐deficient ROP2 in the wild type. We further showed that PAT4 and SCN1, a ROP regulator, additively mediate the stability and targeting of ROP2. The results presented here indicate that PAT4‐mediated S ‐acylation mediates the membrane association of ROP2 at the root hair apex and provide novel insights into dynamic ROP signaling during plant tip growth. Significance Statement: This study uncovers the role of Arabidopsis protein S ‐acyl transferase4 (PAT4) in ROP‐mediated root hair elongation.